Міфологічна картина світу як складова поетичного ідіолекту Чеслава Мілоша - Сидяченко, Н. (Матеріали до української етнології, 2007)
The article addresses the issues of context analysis on the micro and macro levels of the poetic idiolect of Czeslaw Milosz as a poetical concept of grass-snake, which is rooted in the pagan myth making the basis of the imagery paradigm with the following semantics: «mediator between this and that world», «deity which influences human fate», and «the sign of fault, penalty, and revenge».